Microultrasound Molecular Imaging of Vascular Endothelial Growth Factor Receptor 2 in a Mouse Model of Tumor Angiogenesis - Joshua J. Rychak; James Graba; Alison M.Y. Cheung; Bina S. Mystry; Jonathan R. Lindner; Robert S. Kerbel; F. Stuart Foster (Molecular Imaging)
High-frequency microultrasound imaging of tumor progression in mice enables noninvasive anatomic and functional imaging at excellent spatial and temporal resolution, although microultrasonography alone does not offer molecular scale data. In the current study, we investigated the use of microbubble ultrasound contrast agents bearing targeting ligands specific for molecular markers of tumor angiogenesis using high-frequency microultrasound imaging. A xenograft tumor model in the mouse was used to image vascular endothelial growth factor receptor 2 (VEGFR-2) expression with microbubbles conjugated to an anti-VEGFR-2 monoclonal antibody or an isotype control. Microultrasound imaging was accomplished at a center frequency of 40 MHz, which provided lateral and axial resolutions of 40 and 90 μm, respectively. The B-mode (two-dimensional mode) acoustic signal from microbubbles bound to the molecular target was determined by an ultrasound-based destruction-subtraction scheme. Quantification of the adherent microbubble fraction in nine tumor-bearing mice revealed significant retention of VEGFR-2-targeted microbubbles relative to control-targeted microbubbles. These data demonstrate that contrast-enhanced microultrasound imaging is a useful method for assessing molecular expression of tumor angiogenesis in mice at high resolution.